The present housing scenario beyond vernacular designs : review of implications on residential energy efficiency - Hj Mohd Ariffin, Noor Aziah (IIUM Press, 2011)
Energy consumption III Malaysia is on the increase and this has much to do with the prosperity of the country and the increasing affluence of her people since Independence in 1957. The paper, beyond vernacular designs, will elucidate the growth ofthe residential sector in contemporary Malaysia and the inevitable energy consumption and to look for causal reasons on the increment. The role of air conditioning is much to be blamed for the rise of residential energy usage in the country and energy efficient measures need to be addressed and made. Designs ofbuildings and houses need to be aware of this actual issue and measures must be made to mitigate this effect.